New Method for Simultaneous Determination of Microcystins and Cylindrospermopsin in Vegetable Matrices by SPE-UPLC-MS/MS - Leticia Díez-Quijada; Remedios Guzmán-Guillén; Ana I. Prieto Ortega; María Llana-Ruíz-Cabello; Alexandre Campos; Vítor Vasconcelos; Ángeles Jos; Ana M. Cameán (Toxins, 2018)
Cyanotoxins are a large group of noxious metabolites with different chemical structure and mechanisms of action, with a worldwide distribution, producing effects in animals, humans, and crop plants. When cyanotoxin-contaminated waters are used for the irrigation of edible vegetables, humans can be in contact with these toxins through the food chain. In this work, a method for the simultaneous detection of Microcystin-LR (MC-LR), Microcystin-RR (MC-RR), Microcystin-YR (MC-YR), and Cylindrospermopsin (CYN) in lettuce has been optimized and validated, using a dual solid phase extraction (SPE) system for toxin extraction and ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) for analysis. Results showed linear ranges (5–50 ng g−1 f.w.), low values for limit of detection (LOD) (0.06–0.42 ng g−1 f.w.), and limit of quantification (LOQ) (0.16–0.91 ng g−1 f.w.), acceptable recoveries (41–93%), and %RSDIP values for the four toxins. The method proved to be robust for the three variables tested. Finally, it was successfully applied to detect these cyanotoxins in edible vegetables exposed to cyanobacterial extracts under laboratory conditions, and it could be useful for monitoring these toxins in edible vegetables for better exposure estimation in terms of risk assessment.